Human listeriosis and paté: a possible association. Issue 6805 (28th September 1991) - McLauchlin, J; Hall, S M; Velani, S K; Gilbert, R J
Abstract : OBJECTIVES--To study trends in human listeriosis and determine possible sources of infection. DESIGN--Descriptive analysis of laboratory reports of human listeriosis together with a survey of subtypes of Listeria monocytogenes isolated from patients and foodstuffs and an interview survey of patients to obtain food histories. SETTING--United Kingdom and Republic of Ireland 1985 to 1990. RESULTS--There was a near doubling in the incidence of human listeriosis in England, Wales, and Northern Ireland between 1985 and mid-1989 followed by a sharp decline. The upsurge in cases was caused largely by two strains of L monocytogenes, which accounted for 30-54% of the annual totals. These strains were less common before 1987 and after July 1989. A survey of paté in England and Wales in July 1989 showed that it frequently contained L monocytogenes. A similar survey in July 1990 showed a reduction in the proportions of samples contaminated. In 1989 patés from a single plant (manufacturer Y) were more likely to be contaminated by L monocytogenes and at higher levels than those from other producers. Most strains of L monocytogenes recovered from manufacturer Y's paté in 1989 were indistinguishable from those responsible for the 1987-9 upsurge in human listeriosis and were uncommon among isolates from patés from other manufacturers and from a wide range of other foodstuffs. Patients infected with the types of L monocytogenes found in paté were significantly more likely to have recently eaten paté than those affected by other strains. The start of the decline in numbers of cases of listeriosis coincided with government health warnings on paté consumption and the suspension of supplies from manufacturer Y. CONCLUSIONS--Contamination of paté was a likely contributory cause of the increase in the incidence of listeriosis between 1987 and 1989.